Signature of Metallic Behavior in the Metal–Organic Frameworks M3(hexaiminobenzene)2 (M = Ni, Cu) - Dou, Jin-Hu; Sun, Lei; Ge, Yicong; Li, Wenbin; Hendon, Christopher H; Li, Ju; Gul, Sheraz; Yano, Junko; Stach, Eric A; Dincă, Mircea (Journal of the American Chemical Society, 2017)
The two-dimensionally connected metal–organic frameworks (MOFs) Ni3(HIB)2 and Cu3(HIB)2 (HIB = hexaiminobenzene) are bulk electrical conductors and exhibit ultraviolet-photoelectron spectroscopy (UPS) signatures expected of metallic solids. Electronic band structure calculations confirm that in both materials the Fermi energy lies in a partially filled delocalized band. Together with additional structural characterization and microscopy data, these results represent the first report of metallic behavior and permanent porosity coexisting within a metal–organic framework.